Dehydrogenation of formic acid over Pd/C catalysts: insight into the cold plasma treatment. Issue 18 (8th July 2020) - Di, Lanbo; Zhang, Jingsen; Craven, Michael; Wang, Yaolin; Wang, Hongyang; Zhang, Xiuling; Tu, Xin
Abstract : Non-thermal plasma treatment has great potential to open a fast and green route for controllable synthesis of highly active supported metal catalysts. Abstract : Safe and efficient generation of renewable hydrogen via dehydrogenation of cheap and sustainable formic acid using supported Pd catalysts has attracted significant interest. Non-thermal (cold) plasma is demonstrably a fast and environmentally friendly method for synthesizing high-performance supported metal catalysts; however, the synthesis mechanism in the plasma treatment of catalysts still remains obscure. In this work, we investigate formic acid dehydrogenation over activated carbon supported Pd catalysts synthesized using four different methods: thermal treatment (Pd/C-C), plasma treatment (Pd/C-P), thermal treatment followed by plasma treatment (Pd/C-CP), and plasma treatment followed by thermal treatment (Pd/C-PC). The influence of different catalyst treatment methods on the characteristics and dehydrogenation performance of the Pd/C catalysts has been evaluated and discussed. The activity of the Pd/C catalysts for formic acid dehydrogenation follows the order: Pd/C-CP > Pd/C-C > Pd/C-P > Pd/C-PC. The turnover frequency (TOFinitial ) over Pd/C-CP is 1.4, 2.9, and 1.4 times higher than that over Pd/C-C, Pd/C-P and Pd/C-PC, respectively. The activation energy for Pd/C-CP (34.6 kJ mol −1 ) is much lower than that reported for monometallic Pd catalysts. The excellent performance of the Pd/C-CP catalyst can be attributed to the small size and high dispersion of Pd nanoparticles, the high concentration of metallic Pd, and the high Pd/C atomic ratio resulting from the migration of the electroneutral Pd species under the Coulomb repulsion effect of the electrons in the plasma. The high performance of the Pd/C-C catalyst was attributed to the small and highly dispersed Pd nanoparticles formed due to the strong interaction between the activated carbon support and PdCl4 2− ions. The Pd/C-P catalyst exhibits poor performance on account of the low reduction rate of PdCl4 2− ions. The poorest performance, from Pd/C-PC, was ascribed to the large size of the Pd nanoparticles that were formed due to the disturbance of the interaction between the activated carbon support and the PdCl4 2− ions during the preparation of the Pd/C-P catalyst. In conclusion, thermal treatment of Pd/C – prepared using a simple incipient wetness procedure – followed by plasma treatment is an effective method for the synthesis of a high-performance Pd/C catalyst.